Professional Values Influence on the Teachers’ Quality of Islamic Secondary School - Haji Musa, Nasuha binti; Mohd Yusoff, Mohd Zailani (Jurnal Ilmiah Peuradeun, 2019)
The quantitative study was designed to acquire in-depth knowledge related to the influence of the teachers’ professional values on teachers’ quality. The study was implemented based on three dimensions of professional value namely ‘Riadhah Ruhiyyah’ (Al-Ghazali, n.d). Hence, this study aims to identify influence of professional values on teachers’ quality. The specific objective of the study aims to examine the level of teachers’ professional values, the level of teachers’ quality and the influence of professional values on the quality of Islamic secondary school teachers. The researcher adopted the quantitative study method by using questionnaires on 360 teachers from the three categories of Kelantan Islamic Foundation (YIK) Islamic Secondary Schools as respondents of the study. Data collected by the researcher is analyzed using the Statistical Package for the Social Sciences (SPSS) version 2.0. The findings show that teachers’ professional values and teachers’ quality is in high level. The result of the regression analysis of this study indicates that professional values do influence the quality of teachers at the Islamic Secondary Schools of the Kelantan Islamic Foundation. In conclusion, this study has shown the level of professional values do influence teacher quality enhancement. Thus, action towards professional values strengthening and quality improvement among teachers should be taken seriously by all levels of the administration of education.